Exploring practical approaches to maximising data quality in electronic healthcare records in the primary care setting and associated benefits. Report of panel-led discussion held at SAPC in July 2014. Issue 5 (18th January 2016) - Dungey, Sheena; Glew, Simon; Heyes, Barbara; Macleod, John; Tate, A. Rosemary
Abstract : Background: Electronic healthcare records provide information about patient care over time which not only affords the opportunity to improve patient care directly through effective monitoring and identification of care requirements but also offers a unique platform for both clinical and service-model research essential to the longer-term development of the health service. The quality of the recorded data can, however, be variable and can compromise the validity of data use both for primary and secondary purposes. Objectives: In order to explore the challenges and benefits of and approaches to recording high quality primary care electronic records, a Clinical Practice Research Datalink (CPRD) sponsored workshop was held at the Society of Academic Primary Care (SAPC) conference in 2014 with the aim of engaging GPs and other data users. Methods: The workshop was held as a structured discussion, led by an expert panel and focused around three questions: (1) What are the data quality priorities for clinicians and researchers? How do these priorities differ or overlap? (2) What challenges might GPs face in provision of good data quality both for treating their patients and for research? Do these aims conflict? (3) What tools (such as data metrics and visualisations or software components) could assist the GP in improving data quality and patient management and could this tie in with analytical processes occurring at the research stage? Results: The discussion highlighted both overlap and differences in the perceived data quality priorities and challenges for different user groups. Five key areas of focus were agreed upon and recommendations determined for moving forward in improving quality. Conclusions: The importance of good high quality electronic healthcare records has been set forth along with the need for a practical user-considered and collaborative approach to its improvement.